Coagulation in pediatric extracorporeal membrane oxygenation: A systematic review of studies shows lack of standardized reporting. Issue 2 (28th March 2022) - Drop, Joppe; Van Den Helm, Suelyn; Monagle, Paul; Wildschut, Enno; de Hoog, Matthijs; Gunput, Sabrina T.G.; Newall, Fiona; Dalton, Heidi J.; MacLaren, Graeme; Ignjatovic, Vera; van Ommen, C. Heleen
Abstract: Objectives: Extracorporeal membrane oxygenation (ECMO) involves complex coagulation management and frequent hemostatic complications. ECMO practice between centers is variable. To compare results between coagulation studies, standardized definitions and clear documentation of ECMO practice is essential. We assessed how study population, outcome definitions, and ECMO‐, coagulation‐, and transfusion‐related parameters were described in pediatric ECMO studies. Data sources: Embase, Medline, Web of Science, Cochrane Library and Google Scholar. Study selection: English original studies of pediatric ECMO patients describing hemostatic tests or outcome. Data extraction: Eligibility was assessed following PRISMA guidelines. Study population, outcome and ECMO‐, coagulation, and transfusion parameters were summarized. Data synthesis: A total of 107 of 1312 records were included. Study population parameters most frequently included (gestational) age (79%), gender (60%), and (birth) weight (59%). Outcomes, including definitions of bleeding (29%), thrombosis (15%), and survival (43%), were described using various definitions. Description of pump type, oxygenator and cannulation mode occurred in 49%, 45%, and 36% of studies, respectively. The main coagulation test (53%), its reference ranges (49%), and frequency of testing (24%) were the most prevalent reported coagulation parameters. The transfusion thresholds for platelets, red blood cells, and fibrinogen were described in 27%, 18%, and 18% of studies, respectively. Conclusions: This systematic review demonstrates a widespread lack of detail or standardization of several parameters in coagulation research of pediatric ECMO patients. We suggest several parameters that might be included in future coagulation studies. We encourage the ECMO community to adopt and refine this list of parameters and to use standardized definitions in future research.